(3GdOdjd GdefgLj aj EYOGO GdePcQGJ h GdQSGFd GdLGeYjI aj Yde GdGLJeGY (B/s - (3SHYhf, SYjOs ((3GdLRGFQ (B:s (3OGQ GdbUHI ddfTQ ,s, 2012)
(3Gf gPG dOdjd gh ESgGe aj Jchjf fhY ef GdKbGaI GdefgLjI dOi GdWGdH h GdHGMK Ydi GdShGA h gh jQjO Gf jSO aQGZG ajeG jNU GdeGOI GdefgLjI GdYedjI (B. (3jSYi gPG GdOdjd Gdi GdGLGHI Yf cKjQ ef GdJSGDdGJ GdJj JhGLg GdWGdH h GdHGMK YfOeG jJYdb GdGeQ HGdbjGe HHMK SSjhdhLj h jYQV ef efXhQ Yedj GSG Gge GdNWhGJ h GdeQGMd GdefgLjI GdJj gj eMWGJ QFjSjI aj GfLGR GdHMK Gfg HeKGHI RGO eQGab h jecf GSJNOGeg ceYde fSJWjY GdGYgJOGA Hg aj WQjb GdHMK GdYdej GdShSjhdhLj s
Keywords: (3Yde GdELJeGYs; (3efgLjI GdHMKs